Gastroesophageal Reflux in Athletes: Impact on Performance and Non-Surgical Management Strategies - Ząbek, Adam Jan; Kuźniar, Jakub Paweł; Chrzanowska, Emilia Gabriela; Zagalska, Michalina; Turek, Marta; Tamborski, Tomasz; Grzebinoga, Adam; Szlążek, Julia; Roguska, Barbara (Quality in Sport, 2025)
Abstract Introduction: Gastroesophageal reflux disease (GERD) is a common gastrointestinal disorder that can negatively impact athletic performance. Symptoms such as heartburn, regurgitation, and chronic cough may limit exercise capacity and reduce training comfort. This study aims to present the effects of GERD on athletic performance and effective management strategies for athletes. Methods: A literature review was conducted, analyzing 31 scientific articles retrieved from PubMed and Google Scholar. The study examined GERD epidemiology, pathophysiological mechanisms, symptoms, and available treatment and lifestyle modification strategies. Results: GERD is more prevalent among athletes involved in endurance and strength sports, where intense exertion increases intra-abdominal pressure and weakens lower esophageal sphincter (LES) function. Symptoms can lead to reduced performance and exercise-related discomfort. Management strategies include dietary modifications, adjustments in exercise type and intensity, pharmacotherapy (proton pump inhibitors, prokinetic agents), and behavioral techniques such as stress control and sleep hygiene improvement. Conclusions: GERD poses a significant challenge for athletes, affecting their comfort and exercise capacity. Individualized management strategies, including dietary adjustments, tailored training modifications, and pharmacotherapy, can improve quality of life and sports performance. Further research is needed to better understand the impact of different physical activities on GERD and the efficacy of current treatment options.